Cancer-related CD15/FUT4 overexpression decreases benefit to agents targeting EGFR or VEGF acting as a novel RAF-MEK-ERK kinase downstream regulator in metastatic colorectal cancer. Issue 1 (December 2015) - Giordano, Guido; Febbraro, Antonio; Tomaselli, Eugenio; Sarnicola, Maria; Parcesepe, Pietro; Parente, Domenico; Forte, Nicola; Fabozzi, Alessio; Remo, Andrea; Bonetti, Andrea; Manfrin, Erminia; Ghasemi, Somayehsadat; et al.
Abstract Background Cancer-related immune antigens in the tumor microenvironment could represent an obstacle to agents targeting EGFR "cetuximab" or VEGF "bevacizumab" in metastatic colorectal cancer (mCRC) patients. Methods Infiltrating immune cells into tumor tissues, cancer-related expression of immune antigens (CD3, CD8, CD68, CD73, MPO, CD15/FUT4) from 102 mCRC patients receiving first-line Cetuximab or Bevacizumab plus chemotherapy were assessed by immunohistochemistry and validated in an independent tissue microarrays of 140 patients. Genome-wide expression profiles from 436 patients and 60 colon cancer cell lines were investigated using bioinformatics analysis.In vitro kinase assays of target genes activated by chemokines or growth factors were performed. Results Here, we report that cancer-related CD15/FUT4 is overexpressed in most of mCRCs patients (43 %) and associates with lower intratumoral CD3+ and CD8+ T cells, higher systemic inflammation (NLR at diagnosis >5) and poorer outcomes, in terms of response and progression-free survival than those CD15/FUT4-low or negative ones (adjusted hazard ratio (HR) = 2.92; 95 % CI = 1.86–4.41;P  < 0.001). Overexpression ofCD15/FUT4 is induced through RAF-MEK-ERK kinase cascade, suppressed by MEK inhibitors and exhibits a close connection with constitutive oncogenic signalling pathways that respond toERBB3 orFGFR4 activation (P  < 0.001).CD15/FUT4- high expressing colon cancer cells with primary resistance to cetuximab or bevacizumab are significantly more sensitive to MEK inhibitors than CD15/FUT4-low counterparts. Conclusion Cancer-related CD15/FUT4 overexpression participates in cetuximab or bevacizumab mechanisms of resistance in mCRC patients. CD15/FUT4 as a potential target of the antitumor immune response requires further evaluation in clinical studies.